2022-RA-1253-ESGO CONCERVE study demonstrates that clinical regression of high-grade cervical intraepithelial neoplasia is associated with absence of FAM19A4/miR124–2 DNA methylation. (20th October 2022) - van Trommel, Nienke; Kremer, Wieke; Dick, Stèfanie; Heideman, Danielle; Steenbergen, Renske; Bleeker, Maaike; Verhoeve, Harold; van Baal, Marchien; Kenter, Gemma; Meijer, Chris; Berkhof, Johannes
Abstract : Introduction/Background: Cervical screening can prevent cancer by detection and treatment of cervical intraepithelial neoplasia grade 2 or 3 (CIN2/3). Screening also results in considerable overtreatment possibly causing complications, unnecessary anxiety and costs, and preterm birth because many CIN2/3 lesions show spontaneous regression when left untreated. Therefore there is a clinical need for a test predicting spontaneous regression in CIN2/3 lesions. In this multicenter longitudinal cohort study of women with untreated CIN2/3, the prognostic value of FAM19A4/miR124–2 methylation was evaluated for clinical regression. Methodology: We prospectively followed women with CIN2/3 for 24 months. Surgical excision was replaced by a wait-and-see policy. FAM19A4/miR124–2 methylation was evaluated on all clinician-collected samples and self-collected samples collected at baseline. Every 6 months, human papillomavirus (HPV) testing and cytology were conducted on a clinician-collected sample, and a colposcopic examination was performed by a gynecologist to exclude progression. At 24 months at the final study visit, two biopsies were taken. Clinical regression was defined as histologically confirmed absence of CIN2+ or an HPV-negative clinician-collected sample with normal cytology. Regression incidences were estimated using the Kaplan-Meier method. Results: 80/114 women included were diagnosed with CIN2 and 34/114 with CIN3. During the study, 65.8% of women (75/114) did not receive surgical treatment. Women with a negative FAM19A4/miR124–2 result on the baseline clinician-collected sample showed more clinical regression (74.7%) than women with a positive methylation result (51.4%, P=0.013). Regression in women with a negative FAM19A4/miR124–2 methylation test was highest when cytology was atypical squamous cells of undetermined significance/low-grade squamous intraepithelial lesion (88.4%) or HPV16 was negative (85.1%). Conclusion: Most women with untreated CIN2/3 and a negative baseline FAM19A4/miR124–2 methylation test showed clinical regression. Methylation, in combination with cytology or HPV genotyping, can be used to support a wait-and-see policy in women with CIN2/3